Magnetic measurements of superconducting NdFeAsO0.82F0.18 oxypnictide - Pissas, M.; Stamopoulos, D.; Ren, ZA; Shen, XL; Yang, J.; Zhao, Z.X. (SUPERCONDUCTOR SCIENCE & TECHNOLOGY, 2009)
By means of magnetic measurements we have studied the magnetic properties of the NdFeAsO0.82F0.18 superconductor. We estimated the upper critical field H-c2(ab) (T) from the temperature at which the inverse magnetization deviates from linear behavior. Low field magnetic measurements revealed that a external magnetic induction of B = 0.01 T destroys the superconducting path between grains (weak-link behavior). Nd ions behave as isolated paramagnetic centers. This is evident since for magnetic inductions larger than 0.5 T a paramagnetic moment arises from the Nd that overcomes the superconducting diamagnetic signal. Hysteresis loops at several temperatures revealed that the critical current falls rapidly with temperature. The temperature variation of the reversible magnetization shows a behavior that is reminiscent of high-T-c cuprates, indicating the important role of thermal fluctuations.